2008
DOI: 10.1063/1.2963366
|View full text |Cite
|
Sign up to set email alerts
|

Optical pump-probe measurements of sound velocity and thermal conductivity of hydrogenated amorphous carbon films

Abstract: In this paper, we report the measurements of the thermal conductivity and longitudinal sound velocity of four types of hydrogenated amorphous carbon films. The measurements were made with an ultrafast optical pump-probe apparatus. The films were deposited at various temperatures by plasma enhanced chemical vapor deposition. The films are of a low density (1.0–1.4 g cm−3) and are found to have sound velocities that range from as low as 3 km/s to as high as 10 km/s. The thermal conductivities are between 0.6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…2a. Firstly, the simulations are in good qualitative agreement with the available experimental data [3][4][5][6][7][8][9][10], particularly given the magnitude of the experimental uncertainties. Secondly, the linear dependence on density is close to that measured experimentally by Shamsa et al, [4], with the gradients differing by just 20%.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…2a. Firstly, the simulations are in good qualitative agreement with the available experimental data [3][4][5][6][7][8][9][10], particularly given the magnitude of the experimental uncertainties. Secondly, the linear dependence on density is close to that measured experimentally by Shamsa et al, [4], with the gradients differing by just 20%.…”
supporting
confidence: 63%
“…Ref [3] Ref [4] Ref [5] Ref [6] Ref [7−8] Ref [8] Ref [9] Ref [10] diamonds in Fig. 2) exhibits no such variability, finding little deviation from a straight line fitted through the simulation data points.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have shown that the phonon velocity and specific heat of amorphous carbon (a-C) mainly depend on the content of C-C sp 2 and C-C sp 3 bonding [37][38][39]. Thus, we suppose the a-C layer in this work could have a phonon velocity and specific heat approximate to the crystalline graphite, since it is derived from the crystalline graphite that could have a high proportion of C-C sp 2 bonding and can be essentially regarded as the graphite in the short range.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…The lack of lattice periodicity and correlated behaviour at remote distances within the carbonaceous material reduce the mean free path of the energy carriers (both electrons and phonons), and degrade the efficiency of energy transmission. Together with graphene, its close relative-the quasi-one-dimensional carbon nanotube, is comparatively more conductive than the non-crystalline phases including amorphous carbon, [11][12][13][14][15][16][17][18] glassy carbon, 19,20 and pyrolytic char. 21 Consequently, this triggers the notion to explore ways to convert the disordered phases to their graphitic counterparts in order to improve the conductance of electric and thermal energy.…”
Section: Introductionmentioning
confidence: 99%